Understanding the Role of Social Media Marketing and Technology Adoption Model in Shaping Customer Adoption of Digital Banking - Basoeki, Jonathan Bagus Pradhana; Agus, Anna Amalyah (UI Scholars Hub, 2023)
Research Aims: The present research aims to investigate factors that significantly influence customers’ behavioural intention to use digital banking products. Following prior work on social media marketing and the influence of conglomerate group benefits, in addition to providing a comprehensive understanding, the research incorporates three established theories: the Theory of Planned Behaviour, the Technology Acceptance Model, and the Unified Theory of Acceptance and Use of Technology. Design/Methodology/Approach: The sample consists of current Allo Bank users. Data collection involved convenience sampling and a self-administered online questionnaire filled out by 262 respondents in Jakarta, Indonesia. The data analysis technique used was SEM PLS. Research Findings: This study’s findings show that each hypothesis has positive and significant results. Theoretical Contribution/Originality: This study explores the impact of conglomerate group benefits and the influence of social media marketing on consumers’ behavioural intention to use digital banking. Managerial Implications in the South East Asian Context: This study offers insights on how to enhance the behavioural intention to use digital banking. It suggests that subjective norms can have a substantial impact, so encouraging more individuals to utilise digital banking can increase customers’ willingness to adopt. Furthermore, increasing sales promotions while enhancing the perceived behavioural control of customers can also significantly influence adoption. Research Limitations & Implications: The research is constrained to digital banks belonging to conglomerates. This restriction overlooks various other factors that may impact the choice of utilising a digital banking product.